Application of a Current and Voltage Mixed Control Mode for the New Fast Control Power Supply at EAST - 黄海宏 晏腾 王海欣 (Plasma science & technology, 2014)
A feedback control system is needed to restrain plasma vertical displacement in EAST （Experimental Advanced Superconducting Toknmak）. A fast control power supply excites active feedback coils, which produces a magnetic field to control the plasma＇s displacement. With the development of EAST, new demands on the new fast control power supply have led to an enhanced ability of fast response and output current, as well as a new control mode. The structure of cascaded and paralleled H-bridges can meet the demand of extended capacity, and digital control can reMize current and voltage mixed control mode. The validity of the proposed scheme is confirmed by experiments.